A Regularized Gradient Projection Method for the Minimization Problem - Yonghong Yao; Shin Min Kang; Wu Jigang; Pei-Xia Yang (Journal of Applied Mathematics)
We investigate the following regularized gradient projection algorithm xn+1=Pc(I−γn(∇f+αnI))xn, n≥0. Under some different control conditions, we prove that this gradient projection algorithm strongly converges to the minimum norm solution of the minimization problem minx∈Cf(x).